The social capital of entrepreneurial newcomers : bridging, status-power and cognition - Lee, Robert (Palgrave pivot., 2017)
'Lee takes the oft cited belief that entrepreneurial endeavour lives and dies by the quality of the networks set in play, and subjects it to a rigorous and sustained analysis. In this he not only provides the reader with an authoritative theoretical and empirical foray into how entrepreneurs can create and sustain different forms of social capital, he does so with a strong sense of how power frames and taints its acquisition and use. Lee¹s book is a valuable contribution to our understanding of how in entrepreneurial activity, as in many walks of life, it is those with already established status who set the agenda by which opportunity and its pursuit is constituted'. Robin Holt, Professor of Entrepreneurship, Politics and Society, Copenhagen Business School, Denmark This book presents a novel and intellectually stimulating account of the understudied links between entrepreneurial newcomers' bridging ties and their networked cognition. With a paucity of research addressing cognitively specific features of networked language and conduct, The Social Capital of Entrepreneurial Newcomers explores how entrepreneurial newcomers attune their cognition when interacting with high status and powerful vertical bridges. Largely reflecting communication accommodation perspectives, the author theoretically and empirically examines entrepreneurial newcomers' cognitive 'convergence' and 'divergence' when bridging. Robert Lee is a Senior Lecturer in Innovation and Entrepreneurship at Manchester Metropolitan University, UK, and a member of the Centre for International Business and Innovation (CIBI). He has recently completed a British Academy/Leverhulme funded project as principal investigator, researching subjective wellbeing and innovation.